2007
DOI: 10.1007/s10162-006-0065-4
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Deep Electrode Insertion on Cochlear Implant Fitting

Abstract: Using long Med-El Combi40+ electrode arrays, it is now possible to cover the whole range of the cochlea, up to about two turns. Such insertion depths have received little attention. To evaluate the contribution of deeply inserted electrodes, five Med-El cochlear implant users were tested on vowel and consonant identification tests with fittings with first one, two, and up to five apical electrodes being deactivated. In addition, subjects performed pitch-ranking experiments, using loudness-balanced stimuli, to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
85
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(92 citation statements)
references
References 38 publications
6
85
0
Order By: Relevance
“…Some of the factors that limit spatial resolution by cochlear implant users, notably those associated with the speech processor and electrode array, can be mitigated by improvements in technology. For example, deeper insertion of electrode arrays allows for less compression of the basic frequency-to-place map Shannon, 2003, 2005;Gani et al, 2007). Similarly, the implementation of current steering in speech processing strategies can potentially reduce limitations related to fixed electrode locations by allowing current peaks to be "steered" to varying locations between pairs of adjacent electrodes (McDermott and McKay, 1994;Busby and Plant, 2005;Donaldson et al, 2005;Kwon and van den Honert, 2006;Firszt et al, 2007;Koch et al, 2007).…”
Section: F Implications For Speech Recognitionmentioning
confidence: 99%
“…Some of the factors that limit spatial resolution by cochlear implant users, notably those associated with the speech processor and electrode array, can be mitigated by improvements in technology. For example, deeper insertion of electrode arrays allows for less compression of the basic frequency-to-place map Shannon, 2003, 2005;Gani et al, 2007). Similarly, the implementation of current steering in speech processing strategies can potentially reduce limitations related to fixed electrode locations by allowing current peaks to be "steered" to varying locations between pairs of adjacent electrodes (McDermott and McKay, 1994;Busby and Plant, 2005;Donaldson et al, 2005;Kwon and van den Honert, 2006;Firszt et al, 2007;Koch et al, 2007).…”
Section: F Implications For Speech Recognitionmentioning
confidence: 99%
“…This compression may make achieving spatial selectivity between apical stimulation channels increasingly difficult. Thus, increased channel interaction may explain, at least in part, the results of psychophysical studies that indicate that the performance increase achieved with very deeply inserted electrodes (up to 720°) is minimal for many subjects [40][41]. In addition, temporal bone studies using deeply inserted electrodes of the same design resulted in significantly increased trauma compared with moderate depth insertions [25].…”
Section: Figurementioning
confidence: 92%
“…Seven of the nine subjects tested showed improvements on at least one of four speech-recognition tests when switched to the reduced-site maps. Several recent studies have also shown that removing some sites from the processor map can result in improved speech recognition, although the effects depend on the subjects and on what other conditions are changed (Arnoldner et al, 2007;Finley et al, 2007;Gani et al, 2007). In the remainder of this section, we will discuss additional data and considerations relevant to a more general development of the site-selection strategy.…”
Section: Site-removal Strategiesmentioning
confidence: 99%